Attempting to destroy a people by attacking their way of knowing: A case study of the northern Cheyenne - Frank C. Rowland (Adult Education Research Conference, 1995)
Interviews were conducted with elders to understand the Northern Cheyenne way of knowing. Both positive factors about the nature of Cheyenne learning and negative elements concerning the attempt to destroy the Cheyenne way of knowing were uncovered. The results suggest that problems on the reservation can best be understood from an educators perspective concerning the nature of knowing.